Are the vaccines halal? Covid-19, vaccines and vaccination for preservation of life - Ab Rahman, Jamalludin; Nik Mohamed, Mohamad Haniki; Sitiris, Miszairi (Revon Media Sdn. Bhd., 2021)
The Moderna Covid-19 vaccine contains the following ingre- dients: messenger ribonucleic acid (mRnA), lipids (SM-102, polyethene glycol [PEG] 2000 dimyristoyl glycerol [DMG], cholesterol, and 1,2-distearoyl- sn-glycerol-3-phosphocholine [DSPC]), tromethamine, tromethamine hydrochloride, acetic acid, sodium acetate, and sucrose. T h e P f iz er -B i o n Te c h C o v i d-19 vaccine (Comir naty®) includes the following ingredients: mRnA , lipids ((4-hydroxybutyl)azanediyl)bis(hexane-6,1- diyl)bis(2-hexyldecanoate), 2 [(polyethylene glycol)-2000]-n,n-ditetradecylacetamide, 1,2-distearoyl-sn-glycero-3-phosphocholine, and cholesterol), potassium chloride, mono- basic potassium phosphate, sodium chloride, dibasic sodium phosphate dihydrate, and sucrose.